2019
DOI: 10.4103/ajts.ajts_44_18
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bone marrow-derived mononuclear stem cells for neurological recovery in participants with spinal cord injury: A randomized controlled trial

Abstract: BACKGROUND:Complete lesion after spinal cord injury (SCI) remains irreversible with little hope of neurological recovery. Newer interventions such as re-stimulation of damaged neurons using artificial agents and the use of stem cells for neuronal regeneration have shown promising results.AIM:This study was undertaken for evaluating the neurological status of acute SCI participants after stem cell augmentation and comparing them with other treatment methods.SETTING AND DESIGN:Randomized controlled trial in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…It is worth noting that the ASIA score-based assessment of sensory and motor function relies on subjective evaluation by the assessor and the patient, reducing result reliability to a certain extent [ 88 ]. Although this observed rate of 48.9% is lower than the rate of 78.57% obtained by Srivastava et al in a randomized controlled trial with 200 patients [ 69 ] and the rate of 70% observed by Cheng et al [ 31 ], given that small functional improvements are also extremely important for patient survival and well-being, stem cell therapy for SCI remains promising. Meanwhile, an increasing number of patients believe that the recovery of intestinal and bladder functions is as or more important than walking.…”
Section: Discussioncontrasting
confidence: 58%
“…It is worth noting that the ASIA score-based assessment of sensory and motor function relies on subjective evaluation by the assessor and the patient, reducing result reliability to a certain extent [ 88 ]. Although this observed rate of 48.9% is lower than the rate of 78.57% obtained by Srivastava et al in a randomized controlled trial with 200 patients [ 69 ] and the rate of 70% observed by Cheng et al [ 31 ], given that small functional improvements are also extremely important for patient survival and well-being, stem cell therapy for SCI remains promising. Meanwhile, an increasing number of patients believe that the recovery of intestinal and bladder functions is as or more important than walking.…”
Section: Discussioncontrasting
confidence: 58%
“…In the rat SCI model of severe contusion injury, no stem cell treatment has so far succeeded in repairing the tissue loss in the lesion center. Despite this, a benefit on functional recovery is observed justifying clinical trials [8,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, in preparatory experiments we found that spinal cord injection per se caused additional damage. This application may be more effective for interventions in the chronic phase, when cells can be implanted into the cavity within the spinal cord that has formed by then [11,28].…”
Section: Steroid Treatment and Limitations Of The Present Studymentioning
confidence: 99%
“…BM-MSCs promote axonal regeneration by guiding nerve fibers and hence eliminate glial scars in the injured spinal cord [27][28][29]. The precise mechanism by which transplantation of bone marrow-derived MSCs (BM-MSCs) promotes functional recovery after SCI is still unclear [30][31]. Cell transplantation is a targeted new promising therapeutic strategy for spinal cord regeneration based on a series of animal and clinical studies, and it has been previously reported that stem cells have a potential effect on the SCI treatment [32-33, 24, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Song et al 2020[16] Albu, et al 2021[20] Yoon, et al 2007[23] El-Kheir, et al 2014[25] Kishk NA, et al 2010[27] Sharma A, et al 2020[29] Park, et al 2012[31] e218 Role of stem cells transplantation for patients with spinal cord injury: systematic meta-analysis J Popul Ther Clin Pharmacol Vol 30(7):e211-e221; 06 April 2023. This article is distributed under the terms of the Creative Commons Attribution-Non Commercial 4.0 International License.…”
mentioning
confidence: 99%